2004
DOI: 10.2165/00003088-200443080-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profile of Intramuscular Fulvestrant in Advanced Breast Cancer

Abstract: The intramuscular formulation of fulvestrant displays predictable kinetics and approximately 2-fold accumulation on administration once monthly. At the proposed therapeutic dosage (250 mg once monthly), plasma fulvestrant concentrations are maintained within a narrow range throughout the administration interval, thus ensuring stable systemic drug exposure during long-term treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 6 publications
3
48
0
Order By: Relevance
“…The greater effect of fulvestrant 500 mg on Ki67, ER, and PgR at 4 weeks may be at least partly attributable to the loading element of the fulvestrant 500 mg regimen, since steady-state plasma levels should have been reached at 4 weeks, whereas steady-state levels would not have been reached with fulvestrant 250 mg at this time [10].…”
Section: Discussionmentioning
confidence: 99%
“…The greater effect of fulvestrant 500 mg on Ki67, ER, and PgR at 4 weeks may be at least partly attributable to the loading element of the fulvestrant 500 mg regimen, since steady-state plasma levels should have been reached at 4 weeks, whereas steady-state levels would not have been reached with fulvestrant 250 mg at this time [10].…”
Section: Discussionmentioning
confidence: 99%
“…1B, 85.9 Ϯ 8.6% increase in neuronal viability compared with ␤-amyloid 1-42 alonetreated cultures; ‫,ءء‬ P Ͻ 0.01). Based on these analyses, we selected 50 ng/ml (82.4 nM), a relatively low and clinically relevant concentration of ICI 182,780 (Howell et al, 1996;Robertson et al, 2004), for subsequent comparative analyses of the impact of ICI 182,780 on the molecular mechanisms underlying estrogen-inducible neurotrophism and neuroprotection Although the full spectrum of molecular mechanisms that underlie estrogen promotion of neuronal plasticity and survival remains to be elucidated, a number of cellular responses have been well documented . Key among these is 17␤-estradiol regulation of intracellular Ca 2ϩ signaling .…”
Section: Ici 182780 Promoted Neuronal Survival Against Neurodegeneramentioning
confidence: 99%
“…Across reviewed trials, the standard dose and schedule reported for fulvestrant was a single 250 mg IM injection, [59] and a pharmacokinetic analysis of Trial 0020 and Trial 0021 [60], comparing between the different modes of injection, found no evidence of pharmacokinetic or tolerability difference suggesting a similar clinical efficacy, although these studies were not likely powered or designed to evaluate efficacy. Contrary to the Std schedule, a loading dose (LD) schedule was employed in the EFECT trial [20] as well as in several ongoing Phase III trials ( [23] have suggested that patients with hormonereceptor-positive tumours benefit more so than patients with non-receptor-positive tumours.…”
Section: Discussionmentioning
confidence: 99%